ANALISIS PENGELOLAAN ASET TETAP PADA BADAN PENGELOLAAN KEUANGAN DAN ASET DAERAH (BPKAD) KUTAI KARTANEGARA - Arifin, Arfiati - (EKONOMIA, 2019)
Utilization regional property is one the problems often occurs in every government agency because of a lack of understanding and development in implementing its implementation well. The aim to be achieved in this study is to analyze the management fixed assets in the Regional Financial and Asset Management Agency (BPKAD) Kutai Kartanegara.The method used is a statement of applicable government standards, a comparative method of research that compares the management of fixed asset management institutions, by the state with government accounting standards No. According to Dean J. Champion. Management of fixed assets in financial management bodies and regional assets, state cards are matched to fit 87.1% and tasting hypotheses, the hypothesis is rejected because it complies with government accounting standards (PSAP) No. 07.While the use of fixed assets in BPKAD is not fully maximized because it only uses use and lease loans. Fixed assets reginal property is carried out by the asset sector in the Regional Financial and Asset Management Agency Kutai Kartanegara card as management assistant in accordance with government accounting standards No. 07. Concerning fixed assets but not fully maximized, such as utilization in financial institutions and management regional assets are limited to leasing and borrowing